KARAKTERISASI BATANG DAN DAUN TANAMAN AREN DI KABUPATEN PANDEGLANG, SERANG, DAN LEBAK - Yusi Meilani; Nurmayulis Nurmayulis; Susiyanti Susiyanti (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2019)
ABSTRACTSugar Palm (Arenga pinnata Merr,) has a high economic value and has the potential to be exported and can be processed into a variety of food and non-food products. Sugar palm is a multipurpose tree because all parts of the tree can be used, such as stems, palm sap, leaves. Characterization of local palm trees had been carried out in Pandegelang, Serang, and Lebak Regencies (Banten Province) which were used as making nursery material to make better sugar palm in the future (superior varieties). This study used a survey method based on guidelines for plantation germplasm management from the Indonesian Plantation Research and Development Center. The results showed the diversity of stems and leaves of palm trees in the three districts. The diversity of stem phenotypes on sugar palm was seen in the height and circumference of the stem. Diverse appearance of palm leaves seen in the length and circumference of the ptiole, the length of the rachis, the length and width of the leaflets. The study conclude that the accessions used in this study showed variations in the appearance of stems and leaves from the accessions of palm trees observed.